Human resource management in global economy: A link to organisational commitment - Law, Cindy Sing Ling; Mustafa, Rujhan (Universiti Utara Malaysia, 2005)
This survey studies the relationship between selected human resource management practices (leadership, motivation, training) with organizational commitment in 3-star, 4-star and 5-star hotels in Kuching. 143 respondents answering the questionnaires were selected through simple random sampling stratified by departments. The correlation results show that there is a significant (p<0.05) relationship between task-oriented leadership (r=.345), people-oriented leadership (r=.450) and motivation (r=.454) with organisational commitment but there is no significant relationship (p>0.05) between training and organisational commitment. The linear regression results show that motivation predominantly influences organizational commitment. Overall, there is a significant average direct relationship between human resource management practices and organisational commitment in the hotel industry (p<0.05, r=.567).